1975
DOI: 10.1111/j.1365-2222.1975.tb01848.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of nasal polyps with intranasal beclomethasone dipropionate aerosol

Abstract: Summary In a double‐blind trial thirty‐five patients with moderately‐severe nasal polyposis were treated with intranasal beclomethasone dipropionate aerosol for 3 weeks. The dose given (400 γg/day) had only local effect on the symptoms. Judged by diary card scores the nasal symptoms were reduced to 52% of the pre‐trial level for the whole group. Corrected for the placebo effect the percentage was 68. The reduction of symptoms was equally apportioned to the three symptoms, sneezing, nasal secretion and blockage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(51 citation statements)
references
References 4 publications
0
51
0
Order By: Relevance
“…On rare occasions, polyps may arise from the turbinates, and sometimes also from the maxillary sinuses, then constitut ing the so-called antrochoanal polyps. The symptoms, treatment and histology of nasal polyps are well docu mented [1][2][3][4][5][6][7][8], However, in a recent study by Larsen and Tos [9], support is given that the nasal polyp may origi nate from the nasal mucosa, but the study cannot pre clude the presence of underlying ethmoid involvement.…”
Section: Introductionmentioning
confidence: 99%
“…On rare occasions, polyps may arise from the turbinates, and sometimes also from the maxillary sinuses, then constitut ing the so-called antrochoanal polyps. The symptoms, treatment and histology of nasal polyps are well docu mented [1][2][3][4][5][6][7][8], However, in a recent study by Larsen and Tos [9], support is given that the nasal polyp may origi nate from the nasal mucosa, but the study cannot pre clude the presence of underlying ethmoid involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Topical GCS treatment has been shown to reduce polyp size, as well as the associated nasal symptoms (38,71,108). Even more interesting is the finding that GCS treatment after a polypectomy reduces the number of recurrences, especially in patients who have previously been subjected to frequent polypectomies (42,79).…”
Section: Nasal Polypsmentioning
confidence: 89%
“…Several randomized clinical trials have shown these medications to be effective treatments for NP (table 1) [8,13,64,65,66,67,68,69,70,71,72,73,74,75,76]. There are few or no randomized, controlled published trials that evaluate the effectiveness of the INSs flunisolide, triamcinolone, or beclomethasone in polyposis [77].…”
Section: Resultsmentioning
confidence: 99%
“…There are few or no randomized, controlled published trials that evaluate the effectiveness of the INSs flunisolide, triamcinolone, or beclomethasone in polyposis [77]. Two studies with beclomethasone from the 1970s showed significant symptom improvement, but they were likely too short in duration (3 and 4 weeks) to show effects on polyp size [64,65]. …”
Section: Resultsmentioning
confidence: 99%